Does contrast-enhanced computed tomography raise awareness in the diagnosis of the invisible side of celiac disease in adults? - Göya, Cemil; Dündar, İlyas; Özgökçe, Mesut; Türko, Ensar; Özkaçmaz, Sercan; Durmaz, Fatma; Aydın, Mesut; Alabalık, Ulaş; Geylani, Yusuf; Arslan, Mehmet; Hattapoğlu, Salih (Abdominal Radiology, 2022)
Purpose: This study aimed to evaluate the diagnosis and determine major and minor criteria of celiac disease (CD) with the malabsorption patterns (MABP) in the small intestine and colon on computed tomography (CT) and additional CT findings. Methods: This retrospective study was conducted with 116 patients diagnosed with CD, 14 CD patients recovering with treatment, and 35 control patients with non-CD. All patients had CT examinations and histopathological diagnoses. The sensitivity, specificity, PPV, NPV, and accuracy values of each CT finding defined in the literature were statistically evaluated. According to the patient and control groups, the numerical values of the findings and the sensitivity and specificity values were measured according to this cut-off value. The distribution of CT findings according to pathological Marsh data was evaluated in CD patients. Results: Sensitivity and specificity were found to be higher in small bowel MABP findings, mesenteric hypervascularity, and increased SMV/aorta diameter. There was a numerically significant difference in MDCT findings between the control and pathological Marsh groups. In the ROC analysis performed in terms of the total numerical values of each MDCT finding observed between the groups, it was found that there were more than 7 MDCT findings, 100% sensitivity, and 92% specificity. The presence of four major and three minor criteria or three major and four minor criteria were considered significant. Conclusions: Being aware of CT findings below the iceberg that may suggest CD in abdominal CT examinations performed in patients with atypical clinical and malabsorption findings or other nonspecific findings may prevent diagnostic delay and unnecessary procedures.